Effect of NSPRI tin-in-pot compared with pot-in-pot evaporative cooler on the stored fruits - Salaudeen, Kamaldeen Oladimeji; Uzoma, Anugwom; F.F, Olyemi; E.F, Awagu (International Journal of Engineering and Technology, 2013)
The suitability of the humidity chambers known as Evaporative Cooling System (ECS) developed by Nigerian Stored Products Research Institute as storage structures for mangoes were compared for nine days between June-July 2012. Ambient and ECS Temperature throughout the storage period ranges between 27?C- 31?C and 20?C-27?C respectively, while the corresponding relative humidity was 51%-58% and 70%-81% respectively. Colour change and Weight loss were observed as a physical change to determine effect of each selected ECS on the stored mangoes. There is significant range of ripening in tin-in-pot which led to early deterioration of the stored mangoes. Pot –in-pot affects the freshness of the stored mangoes. The overall effectiveness of the tested ECS shows that tin-in-pot is better for the storage of mangoes since for five days, it retains the freshness of the stored mangoes but cannot be used for long due to its natural reaction with the stored fruits.